Manajemen Kepemimpinan Kepala Madrasah dan Pengembangan Keprofesian Berkelanjutan Dalam Peningkatan Mutu Kinerja Guru - Anis Fauzi; Nana Suryapermana; Aen Jaya Rohman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study aims to find out how to overcome the problem of Madrasah Principal Leadership Management and Continuous Professional Development (PKB) in Improving the Quality of Teacher Performance. This research uses a qualitative approach with a case study method. The object of this research is Madrasah Ibtidaiyah Annizhomiyyah, Madrasah Ibtidaiyah Mathla'ul Anwar and Madrasah Ibtidaiyah Az Zahra, Labuan District, Pendeglang Regency. The results of the management of madrasah leadership in improving the quality of teacher performance at Madrasah Ibtidaiyah Annizhomiyah Jaha Labuan are 1) maximizing the learning process even during the covid-19 pandemic; 2) supervision is still carried out and the ability of all teachers to conduct online learning is mapped; 3) overcome the weaknesses and shortcomings of teachers in the online learning process; 4) most teachers take part in online training and webinars through zoom meetings; and 5) all teachers were PKG conducted and the weaknesses of the PKG results were taken seriously by the teachers. Meanwhile, the results of Continuous Professional Development (PKB) management in improving the quality of teacher performance at Madrasah Ibtidaiyah Annizhomiyah Jaha Labuan include 1) teachers understand and are competent in carrying out their duties and functions as teachers; 2) increasing the competence and ability of teachers in managing learning; 3) improving the results of the Teacher Performance Assessment (PKG) and following up on weaknesses found; and 4) increasing teacher performance which has an impact on increasing student achievement.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//